Factors Affecting the Pittsburgh Sleep Quality Index (PSQI) Score in Nursing Students at STIKes Muhammadiyah Ciamis - Nur Hidayat; Suhanda Suhanda; Adi Nurapandi; Rena Lestia Dewi (Jurnal Vocational Nursing Sciences (VNUS), 2019)
Poor sleep quality is a factor in many medical ailments and there is a strong relationship between physical and psychological health. Sleep is a state in which the brain does not process information from sensory neurons and does not give commands to motor neurons. A person's sleep quality can be determined using the Pittsburgh Sleep Quality Index (PSQI) method. The purpose of this study was to describe the factors that influence the value of the Pittsburgh Sleep Quality Index (PSQI) for undergraduate nursing students at STIKes Muhammadiyah Ciamis. The research method used is cross-sectional. The total population is 359 students of STIKes Muhammadiyah Ciamis Nursing Study Program with a research sample of 77 people. The sampling method used the Proportional Random Sampling technique. The results showed that 61 respondents had poor sleep quality, 26 respondents experienced severe stress, 58 respondents experienced a high level of gadget dependence, 48 respondents were in the no smoking category, and 48 people were in the no caffeine consumption category. Based on this research, it can be concluded that the description of sleep patterns in STIKes Muhammadiyah Ciamis Nursing study program students is still dominated by poor sleep quality, so they need to pay attention to improve their sleep quality as an effort to prevent various diseases, improve individual health, and maximize focus and attention. concentration